CARDIAC REMODELING IN ENDURANCE ATHLETES: STRUCTURAL AND FUNCTIONAL ADAPTATIONS TO HIGH-INTENSITY TRAINING - R. Sh. Rajabova; N. M. Nurillaeva; L. Z. Qoraboyeva (Modern American Journals, 2025)
Long-term high-volume endurance training is associated with profound cardiac remodeling, a phenomenon known as the “athlete’s heart.” While generally regarded as a benign and adaptive process, the overlap between physiological remodeling and early manifestations of cardiomyopathies continues to pose diagnostic and clinical challenges. Differentiating normal adaptation from pathology is essential to avoid misdiagnosis, inappropriate disqualification from sports, or, conversely, failure to identify athletes at risk of sudden cardiac death.
Keywords: Cardiac remodeling, Endurance athletes, High-intensity training, Structural adaptations, Functional adaptations, Athlete’s heart, Ventricular hypertrophy, Cardiac function, Exercise physiology, Cardiovascular adaptations.